Library Introduction to The New Student Airlangga University 2016 - Puspitasari, Dewi (Record and Library Journal, 2018)
Big waves influx of new students usually occurs during the reception of new college students at the beginning of the first semester. For that we need a program that can help smooth the socialization of new students to be part of the community college. Library user education is one solution to introduce new students to campus life. Airlangga University Library in 2016 launched a program library 101, commonly known as Introduction to library activities at the New Student Airlangga University (P3MB-UA) in 2016. In this research will discuss library 101 descriptive quantitative. The point of this research are in three (3) aspects. First about mechanism of library 101. Second is the realization of the library 101 and the third is the evaluation of the library 101 The conclusions of this study are 101 Library has been going well. The new student response is very good, is evident from the number of participants is always higher than the target of each session is 20 people and target participants a total of 1,000 people. A total of 101 participants library is 2258 people. Library 101 participantsÂ mostly from faculty and business ekomoni many as 254 people. Participants at least came from the faculty of dentistry, ie 88 people.